Synergistic effects of rosemary, sage, and citric acid on fatty acid retention of palm olein during deep-fat frying - Jaswir, Irwandi; Che Man, Yaakob B.; Kitts, David D. (AOCS Press, 2000)
A study to optimize the use of oleoresin rosemary extract, sage extract, and citric acid in refined, bleached, and deodorized (RBD) palm olein during deep-fat frying of potato chips was performed using response surface methodology. Results showed that the natural antioxidants used in this study retarded oil deterioration, as evidenced by retention of fatty acid profiles. The linoleic to palmitic (C18:2/C16:0) ratio was chosen as the parameter for optimizing the use of natural antioxidants in RBD palm olein during deep-fat frying. Linoleic (R2 = 0.946) and palmitic (R2 = 0.825) acids were found to be the most important dependent variables, giving highest R2 values to various antioxidant treatments after 25 h of frying. All three antioxidants had independent significant (P<0.05) effects on the C18:2/C16:0 ratio. In fact, significant effects on the C18:2/C16:0 ratio of RBD palm olein were also given by a second-order form. A combination of 0.076% oleoresin rosemary extract, 0.066% sage extract, and 0.037% citric acid produced the optimal retention of the essential fatty acid C18:2. In addition, a synergistic effect among these antioxidants on the fatty acid ratio of RBD palm olein was found.